ENVIRONMENT PROTECTION AND ENVIRONMENT MONITORING ISSUES IN THE PROJECTS OF SUBGLACIAL LAKES STUDIES IN ANTARCTICA - I. Alekhina A.; N. Vasiliev I.; V. Lipenkov Ya.; И. Алехина А.; Н. Васильев И.; В. Липенков Я. (Ice and Snow, 2015)
Antarctic subglacial lakes can represent extreme natural habitats for microorganisms from the position of their evolution and adaptation, as well as they can contain the information on Antarctic ice sheet history and climatic changes in their sediments. Now only direct measurements and sampling from these habitats can answer on many fundamental questions. Special precaution should be complied at penetration into these unique relic environments without unfavorable impacts and contamination. A number of recommendations were developed on levels of cleanliness and sterility during direct exploration and research of subglacial environments. Documents considered in the article are the first and necessary steps for appropriate and long-term ecological management of subglacial Antarctic environments. Today there are three projects of subglacial aquatic environment research which are in preparation and realization – the Russian project of Lake Vostok, the similar British project of Lake Ellsworth and the American project on Whillans Ice Stream. The programs of ecological stewardship for direct exploration of these lakes are discussed. All these subglacial aquatic objects of further exploration and research are so various on their structure, age and regime, that only results of all programs as a whole can help to draw us a uniform picture of a subglacial ecological system. Ecological stewardship of these should provide the minimal ecological impact with maximal scientific results. On the basis of existing documents and recommendations the general approaches and the program of ecological stewardship for Lake Vostok research are discussed. Study of drilling fluid, drilling chips, Vostok ice core and the fresh frozen water will allow to make an assessment of biological and chemical contamination as a result of the first penetration and to modify the further stewardship program for the second penetration and direct exploration of lake water. В настоящее время на разных стадиях подготовки и реализации находятся три крупных ...